Microbiological Soil Quality Indicators Associated with Long-Term Agronomical Management of Mediterranean Fruit Orchards - Aissa Arous; Kamel Gargouri; Assunta Maria Palese; Catello Pane; Riccardo Scotti; Massimo Zaccardelli; Gessica Altieri; Giuseppe Celano (Agriculture, 2024)
Soil microorganisms play a crucial role in maintaining soil fertility sensu lato. Sustainable soil management aims to make the soil environment more hospitable increasing microorganism diversity and complexity by means of the minimal disturbance of soil and inputs of organic material. This results in the effective functioning of agricultural systems, better crop productivity, and a reduction in environmental impacts. A study was carried out to evaluate the effects of the long-term application (more than 15 years) of sustainable practices versus conventional ones on soil microbial biomass activity and its functional diversity within different Mediterranean commercial fruit orchards located in Southern Italy. A preliminary survey—performed using the electromagnetic induction technique (EMI)—guided the collection of representative soil samples by reducing the spatial heterogeneity of soil microorganisms. Soil management practices, based on no tillage and the recycling of organic materials of different origins and quality produced within the orchard, increased soil organic carbon, telluric microorganisms activity and their functional diversity compared to ‘non-conservative’ management methods such as continuous tillage. In addition, the rational use of the orchard-inside organic matter (natural/seeded grass cover and pruning material) allowed it to virtuously transform from useless waste into precious resources, eliminating the logistical and economic constraints for their disposal. The simultaneous use of different types of soil management strategies aimed at soil conservation reinforced the positive effects on the microbiological indicators of soil quality rather than the application of a single strategy. This study provides the opportunity to represent what could be the possible evolution of tilled orchards towards more balanced soil conditions when subjected to conservative practices, offering a reference model for fruit growers and technicians who want to improve the stability and the resiliency of their agrosystems.